Maternal and perinatal outcome in patients with severe pre eclampsia/ eclampsia with and without HELLP syndrome - Gupta, T; Gupta, N; Jain, J; Gupta, S; Bhatia, P; Bagla, J (Journal of Universal College of Medical Sciences, 2014)
OBJECTIVE: To evaluate the occurrence of HELLP syndrome inpatients with severe pre eclampsia & eclampsia and to compare the maternal & perinatal outcome in patients with and without HELLP syndrome (partial and true). METHOD: This was a prospective longitudinal study conducted in the Department of Obstetrics & Gynaecology, E.S.I. PGIMSR,NewDelhi from August 2011-April 2013. 50 pregnant women with singleton pregnancy with severe pre eclampsia detected at 28 or more weeks of gestation were enrolled. Patients were divided into three groups: group 1 with severe pre eclampsia, group 2 with severe pre eclampsia with partial HELLP syndrome and group 3 with severe pre eclampsia with true HELLP syndrome. Patients in three groups were compared in regard to maternal complications, gestational age atdelivery, mode ofdelivery, hospital stay andperinatal outcome. RESULTS: Prevalence of HELLP syndrome in severe pre eclampsia was 40% (partial HELLP= 28% and true= 12%). Antenatal and maternal complications were more in true HELLP syndrome patients as compared to other groups. PPH was observed in 40% of entire study group. DIC was found more in true HELLP syndrome patient with high statistically significant p value<0.001 Blood and its product transfusion was more in true HELLP syndrome. There was 100% ICU admission in group 3. In severe pre eclampsia, 11 neonates had birth weight >2.5kg. Where as in partial and true HELLP syndrome, no neonate had birth weight more than 2.5kg.This difference was statistically significant. There was 100% NICU admission in HELLP syndrome, 91.66% in partial HELLP syndrome and 42.3% in severe preeclampsia. The perinatal morbidity and mortality was higher in HELLP syndrome patients than in patient with severe pre eclampsia without HELLP syndrome. CONCLUSION: The study concludes that both maternal and perinatal outcome were adverse in HELLP syndrome than in severe pre eclampsia without HELLP syndrome. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9564 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 7-12